An Online Resource for Monitoring 24-Hour Activity in Children and Adolescents: Observational Analysis - Benny Kai Guo Loo; Siao Hui Toh; Fadzlynn Fadzully; Mohammad Ashik Zainuddin; Muhammad Alif Abu Bakar; Joanne Shumin Gao; Jing Chun Teo; Ethel Jie Kai Lim; Beron Wei Zhong Tan; Michael Yong Hwa Chia; Terence Buan Kiong Chua; Kok Hian Tan (JMIR Publications, 2024)
Abstract BackgroundThe Singapore integrated 24-hour activity guide for children and adolescents was introduced to promote healthy lifestyle behaviors, including physical activity, sedentary behavior, sleep, and diet, to enhance metabolic health and prevent noncommunicable diseases. To support the dissemination and implementation of these recommendations, a user-friendly online resource was created to help children and adolescents adopt these behaviors in Singapore. ObjectiveThis study aimed to assess the acceptability of the resource in the adoption of healthier lifestyle behaviors, and the change in the users' behaviors with the use of this resource. MethodsParticipants aged 7-17 years were required to log their activity levels of the past 7 days at the beginning and at the end of a 3-month period using the browser-based online resource, including information on the duration and frequency of moderate- to vigorous-intensity physical activity (MVPA), length of sedentary behavior, duration and regularity of sleep, and food portions. User satisfaction, on the length, ease of use, and relevance of the online resource, was also recorded using a 10-point Likert scale. Descriptive statistics and statistical analyses, including the Wilcoxon signed rank test and McNemar test, were carried out at baseline and at the end of 3 months. ResultsA total of 46 participants were included for analysis. For physical activity, the number of days of MVPA increased from a median of 3 (IQR 2‐5) days to 4 (IQR 2‐5) days (P=P=P=P=P= ConclusionsThe findings support the development of a dedicated resource to assist the implementation of healthy lifestyle behaviors based on the Singapore integrated 24-hour activity guide for children and adolescents. This resource received favorable ratings and its use showed the adoption of healthier behaviors, including increased physical activity and sleep, as well as decreased sedentary time and carbohydrate consumption, at the end of a 3-month period.